2016
DOI: 10.1016/j.physletb.2016.08.037
|View full text |Cite
|
Sign up to set email alerts
|

On the geometrical interpretation of scale-invariant models of inflation

Abstract: We study the geometrical properties of scale-invariant two-field models of inflation. In particular, we show that when the field-derivative space in the Einstein frame is maximally symmetric during inflation, the inflationary predictions can be universal and independent of the details of the theory.Comment: 14 pages, no figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 33 publications
2
76
0
Order By: Relevance
“…In cosmology there are global [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] or local [28][29][30][31][32][33][34][35][36][37][38][39] scale invariant alternatives to gravity with spontaneous breaking that generates the Planck scale by a non-minimal coupling.…”
Section: Motivationmentioning
confidence: 99%
“…In cosmology there are global [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] or local [28][29][30][31][32][33][34][35][36][37][38][39] scale invariant alternatives to gravity with spontaneous breaking that generates the Planck scale by a non-minimal coupling.…”
Section: Motivationmentioning
confidence: 99%
“…Such scale invariant theories have to generate all dimensionfull scales through spontaneous breaking of the symmetry, including the Planck scale and the electroweak breaking scale associated with the BEH boson. To generate a period of inflation it is also necessary for the spontaneous scale symmetry breaking to give rise to the inflation scale and it has been shown that this is possible in the context of a model with two scalar fields non-minimally coupled to the Ricci scalar, R [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Such models can naturally lead to an acceptable period of inflation and, for the case in which one scalar is identified with the BEH boson, are similar to "Higgs" inflation [22].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Ref. [29][30][31] poles of kinetic term correspond to stretching of the scalar potential around the pole and therefore such theories are the natural source of flat inflationry potentials. For λ = λ 2 and in the n → ∞ limit one finds 17) which is very similar to the kinetic term for of the α-attractors [20], where the kinetic term of a scalar field ψ is equal to (∂ψ) 2 …”
Section: Equivalence To α Attractorsmentioning
confidence: 91%